Analisis Kelayakan Bisnis UMKM Makanan Khas Palembang - Irlan Aldhiansyah; Rama Pratama Nugraha (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2023)
Small and medium enterprises (SMEs) play a strategic role in supporting regional economic growth, particularly in the culinary sector based on local wisdom. Palembang is widely known for its traditional food products such as pempek, kemplang, and various fish-based processed foods that have significant market potential. However, many SMEs still face limitations in evaluating business feasibility comprehensively, which affects sustainability and competitiveness. This study aims to analyze the business feasibility of Palembang traditional food SMEs from market, technical, management, and financial aspects. This research employs a descriptive qualitative approach using case study methods. Data were collected through interviews, observations, and documentation involving SME owners, supported by secondary data from previous studies. The analysis techniques include market potential analysis, production feasibility assessment, management evaluation, and financial analysis using indicators such as Break Even Point, Net Present Value, and Payback Period. The results indicate that Palembang traditional food SMEs are generally feasible to develop, especially due to stable market demand, availability of raw materials, and relatively simple production processes. Financially, most businesses demonstrate positive feasibility indicators. This study concludes that strengthening managerial capabilities, financial planning, and marketing strategies is essential to enhance business sustainability. The findings provide practical implications for SME owners and policymakers in formulating development strategies for local culinary businesses.